PENGARUH MEDIA KONTEN YOUTUBE TERHADAP HASIL BELAJAR IPS SISWA SMP NEGERI 1 BELIMBING HULU - Gabriel Tamakai Buda; Dessy Triana Relita; Munawar Thoharudin (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
One way to support the learning process is to use media. The problem in this research is that the learning outcomes of class VIII students are still low and have not reached the minimum completeness criteria. It is hoped that the use of YouTube media as a learning medium for social studies subjects can make it easier for students to absorb material and be more active in participating in social studies learning activities. The aim of the research is to identify the influence of YouTube content media on student learning outcomes in class VIII social studies subjects. In this research there are 2 variables, namely YouTube content media as the independent variable and student learning outcomes as the dependent variable. The illustrations in this research are class VIII B as the experimental class and class VIII A as the control class. This research uses a quantitative method. The form of research used is an experiment with a quasi-experimental design. Information collection methods and tools use test questions, observation sheets, and documentation. The results of this research show that there is an effect of using YouTube content media on student learning outcomes